Peran Filantropi Lokal dalam Sejarah Kesejahteraan Sosial Indonesia: Kajian Literatur Kualitatif - Hamam Mishbakhuzzein; Dede Saeroji; Dede Ipan Rizky Agung; Mohammad Ridwan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative literature review methodology to examine the influence of local philanthropy on the formation and sustainability of social welfare systems in Indonesia. Local philanthropy has flourished through religious teachings, cultural values, and community-oriented charitable acts since before colonialism. It has become an essential component of the social framework for addressing poverty, natural disasters, and social injustice. This study examines the evolution of traditional local philanthropic organizations, including zakat, infaq, waqf, gotong royong, and village barns, into a structured and formal framework. The study shows that, in addition to strengthening the national welfare system, local philanthropy pursues strategic goals aimed at increasing social capital and fostering citizen unity. This research shows that the revitalization of local philanthropic principles can significantly replace the establishment of an inclusive, dynamic, and sustainable social welfare system in Indonesia.